Growth enhancement and management of Phytophthora - Rot in Vanilla Nurseries using microbial inoculants - Shahida K (Department of Plant Pathology, College of Horticulture, 2007)
A study on “Growth enhancement and management of Phytophthora rot in vanilla nurseries using microbial inoculants” was carried out in the Department of Plant Pathology, College of Horticulture, Vellanikkara. The salient findings are abstracted below: